Local completeness of ℓp(E), 1≤p<∞ - C. Bosch; T. Gilsdorf; C. Gómez; R. Vera (International Journal of Mathematics and Mathematical Sciences)
We study the heredity of local completeness and the strict Mackey convergence property from the locally convex space E to the space of absolutely p-summable sequences on E, ℓp(E) for 1≤p<∞.